Ecological implications of allometric relationships in American alligators (Alligator mississippiensis) - Sergio A. Balaguera-Reina; Brittany M. Mason; Laura A. Brandt; Nicole D. Hernandez; Bryna L. Daykin; Kelly R. McCaffrey; Sidney T. Godfrey; Frank J. Mazzotti (Scientific Reports, 2024)
Abstract Morphometric allometry, the effect of size on morphological variation, has been of great interest for evolutionary biologist and is currently used in fields such as wildlife ecology to inform management and conservation. We assessed American alligator (Alligator mississippiensis) morphological static allometry across the Greater Everglades ecosystem in South Florida, United States using a robust dataset (~ 22 years) and investigated effects of sex, habitat, and sampling area on morphological relationships. Regression models showed very strong evidence of a linear relationship between variables explaining equal to or above 92% of the variation in the data. Most trait–size relationships (8 out of 11 assessed) showed hyperallometry (positive allometry) with slope deviations from isometry between 0.1 and 0.2 units while the other three relationships were isometric. Sampling area, type of habitat, and in a lesser extent sex influenced allometric coefficients (slope and intercept) across several relationships, likely as result of differing landscapes and ecosystem dynamic alterations and sexual dimorphism. We discuss our findings in terms of the biology of the species as well as the usefulness of our results in the context of ecosystem restoration and conservation of the species. Finally, we provide recommendations when using trait–length relationships to infer population nutritional—health condition and demographics.